Turkish Foreign Policy During Ataturk's Era 1920-1938: Caucasia, Balkans, Middle East From Political, Economic, Social and Cultural Aspects - Eraslan, Cezmi (Istanbul University Press, 2021)
The Turkish Republic, proclaimed at the end of the Turkish National Struggle under the leadership of Ataturk, is a state that leans on the heritage of six centuries Ottoman Empire and constructed on the ashes of it. It was naturally brought with continuity about understanding and institutions of state, because the cadre who performed the national struggle and founded the new state was the last generation of the Ottoman Empire. Ataturk continued the reform method of the Ottoman state, which was destroyed after a long experience of reform, with more radical and radical practices. In addition, he acted more realistically in terms of understanding of dominance and did not pursue ideals that the state could not afford. The main goal of this process was limited to realize the principles of the National Pact. It is known that they tried to find possibilities for internal reforms, around the principals of "peace at home, peace in the World". There are lots of research made with a political point of view about the understanding and performances on the foreign policy of Ataturk, the founder of Turkish Republic and the first President. Distinguished scholars Fahir Armaoğlu and Rifat Uçarol have studied the subject in general in their political history books. Ömer Kürkçüoğlu, Mehmet Gönlübol-Cem Sar and Abdulahat Akşin have handled the topic around Ataturk's era and publications of official document like "Ataturk's National Foreign Policy", examined the outline of bilateral political relations in this process. However, the political relations with the states many of them separated from the Ottoman Empire were not evaluated from the social, cultural and economic points of view with the same measure. Of course, the atmosphere that emerged after the First World War, especially the pursuit of revision in the 30s and the effort to maintain the status quo, had a great impact on this circumstance. The political dimension of the relations stood out more than any other aspect. The aim of this study is pointing out mainly social, cultural and economic aspects of bilateral relations. However, it is noteworthy that the political dimension was not neglected in our chapters, because it is a fact that the other aspects could emerge as much as the political developments let. This book focuses on the relations in the triangle of Caucasus, Balkans and the Middle East, after an introduction part that examines Ataturk's foreign policy understanding and activities on the Hatay example. The relations with Russia and Azerbaijan in the Caucasus, the examples of Bulgaria, Greece, Romania and Albania in the Balkans and Iran and Syria in the Middle East are dealt with. Despite our decision and efforts to concentrate our work in the social, cultural and economic sphere, the priority imposed by the conditions of the period required that political relations not be neglected.